EVALUASI PENANGANAN PENYAKIT MULUT DAN KUKU (PMK) DAN LUMPY SKIN DISEASE (LSD) PADA SAPI PERAH: STUDI KASUS DI KOPERASI AGRO NIAGA JABUNG SYARIAH JAWA TIMUR - Sintia Dewi Nilam Kusumah; Mohamad Nurul; Farida Kusuma Astuti (Universitas Tribhuwana Tunggadewi, 2026)
Foot and Mouth Disease (FMD) and Lumpy Skin Disease (LSD) threaten dairy cattle in Indonesia, causing major economic losses. Evaluation of disease management at the cooperative level remains limited. This study evaluated the FMD and LSD management system at Koperasi Agro Niaga Jabung Syariah, East Java, focusing on detection, isolation, treatment, vaccination, biosecurity, and socioeconomic impacts. A descriptive qualitative case study was conducted from September to November 2023. Data were collected from 24 key informants through interviews, observation, and document analysis. Quantitative data were analyzed descriptively. Among 245 dairy cattle, prevalence was 0.4% for FMD and 5.7% for LSD. The recovery rate was 100% with zero mortality. Vaccination coverage was high (FMD: 92.4%; LSD: 98.9%), and response time was 24 hours. However, the biosecurity score was only 32%, and 50% of farmers lacked isolation facilities. Economic losses reached IDR 6.7–9.9 million (FMD) and IDR 5.4–8.7 million (LSD) per case. Milk production dropped 40–75%. Psychological distress affected 87.5% of farmers, and 25% considered exiting the business. Rapid detection, multi-stakeholder coordination, integrated conventional-herbal treatment, and mass vaccination led to successful outcomes. However, weak biosecurity and inadequate isolation remain critical vulnerabilities. Strengthening biosecurity, farmer education, and psychological support is urgently needed.